2006
DOI: 10.1111/j.1365-294x.2006.02889.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread gene flow and high genetic variability in populations of water volesArvicola terrestrisin patchy habitats

Abstract: Theory predicts that the impact of gene flow on the genetic structure of populations in patchy habitats depends on its scale and the demographic attributes of demes (e.g. local colony sizes and timing of reproduction), but empirical evidence is scarce. We inferred the impact of gene flow on genetic structure among populations of water voles Arvicola terrestris that differed in average colony sizes, population turnover and degree of patchiness. Colonies typically consisted of few reproducing adults and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 70 publications
8
80
3
1
Order By: Relevance
“…Second, disturbance is mainly occurring in the NMRS, but silver sagebrush habitat is naturally patchy (Aldridge and Brigham 2003). Peacock and Ray (2001) and Aars et al (2006) found mammal populations inhabiting patchy habitat retain higher levels of genetic variability compared to high-density continuous populations due to efficient and frequent long-distance dispersal. Both sage-grouse subpopulations exhibit IBD, equivalent diversity, and some long-distance dispersal (Table 3).…”
Section: Range Periphery and Fragmentationmentioning
confidence: 98%
“…Second, disturbance is mainly occurring in the NMRS, but silver sagebrush habitat is naturally patchy (Aldridge and Brigham 2003). Peacock and Ray (2001) and Aars et al (2006) found mammal populations inhabiting patchy habitat retain higher levels of genetic variability compared to high-density continuous populations due to efficient and frequent long-distance dispersal. Both sage-grouse subpopulations exhibit IBD, equivalent diversity, and some long-distance dispersal (Table 3).…”
Section: Range Periphery and Fragmentationmentioning
confidence: 98%
“…Although there is a solid theoretical framework explaining the ecological and evolutionary consequences of local colonization and extinction in metapopulations (e.g., Harrison and Hastings 1996;Hanski and Gilpin 1997), including the effect on genetic differentiation among and within demes within a metapopulation (Slatkin 1977;Wade and McCauley 1988;Whitlock and McCauley 1990), empirical studies in natural environments are still quite scarce (Whitlock 1992;Saccheri et al 1998;Aars et al 2006), especially in the marine environment. Theory indicates that the amount of genetic differentiation among demes within a metapopulation is largely dependent upon the mode of founding of new demes within that metapopulation (Wade and McCauley 1988): large propagules with individuals from many demes will cause little genetic differentiation within the metapopulation.…”
mentioning
confidence: 99%
“…Moreover, red squirrels from all six populations showed high levels of heterozygosity at the ten loci and gene diversity H E ranged from 0.49 in COG to 0.61 in VAL (Trizio et al 2005). The number of microsatellite loci used to assign parents in this study was within the range of loci used in other vertebrate studies obtaining successful parentage assignment using CERVUS (four microsatellite markers in the canyon mouse, Shurtliff et al 2005; eight markers, Lemos et al 2006; 12-17 markers for a variety of mammals, Aars et al 2006;Castagnasso et al 2007;Lane et al 2008;up to 22 markers in badgers, Dugdale et al 2007).…”
Section: Discussionmentioning
confidence: 92%
“…In several studies only parents assigned with a 95% probability were considered (e.g., Aars et al 2006;Dugdale et al 2007;Lane et al 2008). In our study system it was impossible to exclude the candidate mothers (CPs) assigned with a 80% confidence (see also Telfer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation